Ethics of a Business Manager: Intercultural Exegesis of Luke 16:1-18 (Hekima Review, 2006)
People in many countries of Africa are perpetrators and victims of socio-economic mismanagement. The proliferation of religious sects is in some ways a spiritual response to this crisis.1 Unfortunately, religious infatuation often overlooks or undermines what the Scripture says about business management. As a result, Christian organisations conduct their business in a manner that leaves a lot to be desired in terms of efficiency, honesty and justice. Ethics of a business manager is an attempt to face this challenge. It also emerges from the need of relating biblical exegesis to Christian ethics. A considerable number of Christians, including professional exegetes, read the Bible and do some business, but very little has been said about biblical paradigms of business ethics. Nonetheless, J.I.H. McDonald finds that the growth of interdisciplinary studies is one of the more rewarding features of the current academic scene, whereby prominence has been given to ethics of biblical interpretation and ethics in the Scripture.